The anti-AChE and anti-proliferative Activities of Glaucium acutidentatum and Glaucium corniculatum Alkaloid Extracts - Fatma Gonca Kocanci, Buket Hamamcioglu, Belma Aslim (Journal of Applied Pharmaceutical Science, 2017)
In this study, methanol and water extracts of Glaucium acutidentatum and Glaucium corniculatum were analysed for anti-AChE activity on neuronal PC12 cell and anti-proliferative activity on HT-29 and HeLa cancer cells. In this study, total alkaloid, phenol and flavonoid content were analyzed for the determination of active compounds of Glaucium acutidentatum and Glaucium corniculatum. Indeed, methanol and water alkaloid extracts of these plants were evaluated for their anti-AChE activities on NGF-differentiated PC12 cells (dPC12) and anti-proliferative activities on HT-29 and HeLa cancer cells. Our data showed that alkaloid was major compound, the different concentrations of plant extracts had 35-90% in vitro AChE inhibitory activity and 26-54% cellular AChE inhibitory activity and it is dose dependent manner. Furthermore, G. acutidentatum methanolic extracts showed the highest anti-proliferative activity in HT-29 cells (45±5%) Both 1000 μg/ml methanolic extracts showed the maximum anti-proliferative effect in HeLa cells (64±3%). In conclusion, this study has shown that the anti-AChE and anti-proliferative effects of these two plants and the presence of a new AChE inhibitor (AChEi) may be effective in AD and cancer.
Keywords: Glaucium spp., Acetylcholinesterase (AChE), Anti-proliferative activity, water and methanol extracts.